2022
DOI: 10.3389/fphar.2022.1036502
|View full text |Cite
|
Sign up to set email alerts
|

Natural products targeting glycolysis in cancer

Abstract: Many energy metabolism pathways exist in cancer, including glycolysis, amino acid metabolism, fatty acid oxidation, and mitochondrial respiration. Tumor cells mainly generate energy through glycolysis to maintain growth and biosynthesis of tumor cells under aerobic conditions. Natural products regulate many steps in glycolysis and targeting glycolysis using natural products is a promising approach to cancer treatment. In this review, we exemplify the relationship between glycolysis and tumors, demonstrate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 137 publications
0
5
0
Order By: Relevance
“…Metabolic reprogramming is a recognized hallmark of malignant transformation [ 3 ], and it has become the subject of intensive research for the design of new therapeutic approaches. The strong dependence of tumors on glycolysis led to the development of a huge number of glycolytic enzyme inhibitors, including natural compounds [ 19 , 20 , 21 ]. However, recent advances have demonstrated that many tumors rely on OXPHOS to meet the energetic demands, thus setting the focus on mitochondrial metabolism [ 9 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic reprogramming is a recognized hallmark of malignant transformation [ 3 ], and it has become the subject of intensive research for the design of new therapeutic approaches. The strong dependence of tumors on glycolysis led to the development of a huge number of glycolytic enzyme inhibitors, including natural compounds [ 19 , 20 , 21 ]. However, recent advances have demonstrated that many tumors rely on OXPHOS to meet the energetic demands, thus setting the focus on mitochondrial metabolism [ 9 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of HIF-1-related signaling genes induced by HSPE suggests that HSPE can participate in cell survival, proliferation, angiogenesis, invasion, metastasis, cancer stemness, and metabolic reprogramming in human skin cells [ 29 ]. Furthermore, several studies suggest that natural products can affect the glycolysis pathway and can be used to inhibit cancer cells [ 30 ]. However, the possible role of HSPE with the suggested functions should be further characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products have the potential to be effective as therapeutic agents because of their lower toxicity and higher specificity than synthetic compounds [15]. A growing interest has been observed in identifying glycolysis inhibitors from natural sources that can be used as safe and effective alternatives [16,17]. These inhibitors have demonstrated promising results in preclinical models [18][19][20].…”
Section: Introductionmentioning
confidence: 99%